Mesquite : an arboreal love affair - Nabhan, Gary Paul (Chelsea Green Publishing, 2018)
As a Franciscan brother and ethnobotanist who has often mixed mirth with earth, laughter with landscape, food with frolic, Nabhan now takes on a large, many-branched question: What does it means to be a tree, or, accordingly, to be in a deep and intimate relationship with one? To answer this question, Nabhan does not disappear into a forest but exposes himself to some of the most austere hyper-arid terrain on the planet<U+2015>the Sonoran and Chihuahuan deserts along the US/Mexico border<U+2015>where even the most ancient perennial plants are not tall and thin, but stunted and squat. There, in desert regions that cover more than a third of our continent, mesquite trees have become the staff of life, not just for indigenous cultures, but for myriad creatures, many of which respond to these “nurse plants” in wildly intelligent and symbiotic ways. In this landscape, where Nabhan claims that nearly every surviving being either sticks, stinks, stings, or sings, he finds more lives thriving than you could ever shake a stick at. As he weaves his arid yarns, we suddenly realize that our normal view of the world has been turned on its head: where we once saw scarcity, there is abundance; where we once perceived severity, there is whimsy. Desert cultures that we once assumed lived in “food deserts” are secretly savoring a most delicious world. Drawing on his half-century of immersion in desert ethnobotany, ecology, linguistics, agroforestry, and eco-gastronomy, Nabhan opens up for us a hidden world that we had never glimpsed before. Along the way, he explores the sensuous reality surrounding this most useful and generous tree.